Analisis Peran Self-Efficacy terhadap Kemampuan Representasi Matematis dalam Model Pembelajaran Inovatif: Sebuah Studi Literatur - Kemal Musyaffa, Wildan; Yuhana, Yuyu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Mathematical representation ability is a crucial foundation for students in constructing concepts and solving mathematical problems, yet its achievement is often hindered by psychological factors such as low self-confidence. This study aims to analyze the role of self-efficacy on students' mathematical representation abilities within the framework of innovative learning models through a systematic literature study. The method employed is a Systematic Literature Review (SLR) of 18 relevant national and international scientific articles. The analysis results show a significant positive correlation between self-efficacy and mathematical representation ability. Students with high self-efficacy are able to flexibly translate between forms of representation, while those with low efficacy tend to face obstacles in symbolic and verbal representations. The findings also emphasize that innovative learning models, particularly Project-Based Learning (PjBL) integrated with technology or the STEAM approach, serve as the most effective intervention strategies. These models provide mastery experiences that simultaneously boost self-confidence and sharpen students' representation skills. In conclusion, strengthening affective aspects through innovative instructional design is the primary key to optimizing mathematical representation abilities at the secondary school level.